Polysaccharides - Properties and Applications - Mohd Imran Ahamed, Rajender Boddula, Tariq Altalhi, Mohd Imran Ahamed, Rajender Boddula, Tariq A. Altalhi (John Wiley & Sons, 2021)
This book provides the whole spectrum of polysaccharides from basic concepts to commercial market applications. Chapters cover various types of sources, classification, properties, characterization, processing, rheology and fabrication of polysaccharide-based materials and their composites and gels. The applications of polysaccharides include in cosmetics, food science, drug delivery, biomedicine, biofuel production, marine, packaging, chromatography and environmental remediation. It also reviews the fabrication of inorganic and carbon nanomaterials from polysaccharides. The book incorporates industrial applications and will fill the gap between the exploration works in the laboratory and viable applications in related ventures.